Fiscal policy over the real business cycle a positive theory - Battaglini, Marco; Coate, Stephen 1957- (Working paper series / National Bureau of Economic Research, 2008)
"This paper presents a political economy theory of the behavior of fiscal policy over the business cycle. The theory predicts that, in both booms and recessions, fiscal policies are set so that the marginal cost of public funds obeys a submartingale. In the short run, fiscal policy can be pro-cyclical with government debt spiking up upon entering a boom. However, in the long run, fiscal policy is counter-cyclical with debt increasing in recessions and decreasing in booms. Government spending increases in booms and decreases during recessions, while tax rates decrease during booms and increase in recessions. Data on tax rates from the G7 countries supports the submartingale prediction, and the correlations between fiscal policy variables and national income implied by the theory are consistent with much of the existing evidence from the U.S. and other countries"--National Bureau of Economic Research web site